Composite repair : theory and design - Duong, Cong N. (Elsevier, 2007)
Bonded composite repairs are efficient and cost effective means of repairing cracks and corrosion grind-out cavity in metallic structures, and composite structures sustained impact and ballistic damages, especially in aircraft structures. This book grew out of the recent research conducted at the Boeing Company and the Defence Science and Technology Organisation (DSTO, Australia) over the past ten years. Consequently it is predominately a compilation of the work by the authors and their colleagues at these two organizations on the design and analysis of composite repairs. Composite Repair is entirely devoted to the design and analysis of bonded repairs, focusing on the mathematical techniques and analysis approaches that are critical to the successful implementation of bonded repairs. The topics addressed are presentated in a sufficiently self-explanatory manner, and serve as a state-of-the-art reference guide to engineers, scientists, researchers and practitioners interested in the underpinning design methodology and the modelling of composite repairs. * The only book devoted entirely to the design and analysis of bonded repairs * Focusing on mathematical techniques and analytical methodologies that are critical to the successful implementation of bonded repair * A companion reference book to the United Stated Air Force (USAF) bonded repair guidelines (Guidelines for Composite Repair of Metallic Structures-CRMS, AFRL-WP-TR-1998-4113) and the Royal Australian Air Force (RAAF) Design Standard DEF(AUST)995 * Covering a variety of topics and effects: repairs of fatigue and sonic fatigue cracks, and corrosion grind-out cavity, and effects of secondary bending, octagon-shaped patches, thermal residual stresses, patches in proximity, patch tapering edge, etc.